8. LIVER CANCER IN VIETNAM AND ASIA FROM 2013 TO 2023: EPIDEMIOLOGICAL TRENDS AND CONTRIBUTING RISK FACTORS – A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2025)
Objectives: This scoping review explored liver cancer incidence, mortality trends, and risk factors in Vietnam and Asia from 2013 to 2023, using the PCC framework (Population, Concept, Context).Methods: Following PRISMA-ScR guidelines, a literature search was conducted using PubMed, Web of Science, and Vietnamese sources. Eligible studies were selected and synthesized thematically to provide a comprehensive view.Results: Thirty-three studies were included. Vietnam and several Asian countries reported some of the highest liver cancer rates globally, with age-standardized incidence rates reaching 20.2 per 100,000 in Vietnam, 25.7 in China, and 31.0 in Mongolia, according to GLOBOCAN 2022 data. Major risk factors include HBV/HCV infections, aflatoxin exposure, alcohol, metabolic disorders, environmental pollution, and poor healthcare access.Conclusions: The burden of liver cancer remains high in Vietnam and Asia. Comprehensive public health interventions addressing both infectious and lifestyle-related factors, along with improvements in healthcare infrastructure, are urgently needed to address the growing health challenges.
Keywords: liver cancer; Vietnam, Asia; incidence; mortality; risk factors; HBV; aflatoxins